Pemikiran Ekonomi Ibnu Khaldun dan Al-Ghazali Serta Relevansinya Terhadap Perekonomian di Indonesia - Rahmat Hidayat; Fiantika Salwa Ibrahim; Mardawati (Journal of Islamic Economic Studies, 2025)
The Islamic economic thought developed by great figures such as Ibn Khaldun and Al-Ghazali has contributed to understanding a just and prosperous economic system. This study examines Islamic economic thought according to Al-Ghazali and Ibn Khaldun and its relevance to the economy in Indonesia. This study uses a descriptive qualitative method with a literature study approach to describe the Prophet's economic policies systematically and analytically. The study results explain that Al-Ghazali emphasized the importance of ethics in economics, including aspects of morality in economic activities, fair distribution of wealth, and avoidance of usury and oppression practices. Meanwhile, Ibn Khaldun, with his "Asabiyah" theory, links economic growth with social strength and solidarity in society, which affects the stability and prosperity of a country. Indonesia's economic challenges include social inequality, poverty, and unemployment, so the thoughts of these two figures can provide solutions based on Islamic values ​​that emphasize balance, justice, and social welfare. The research implications underline that the principles proposed by Al-Ghazali and Ibn Khaldun can be applied in the context of the modern Indonesian economy to achieve sustainable, inclusive, and equitable economic growth